Ipilimumab administration for advanced melanoma in patients with pre-existing Hepatitis B or C infection: a multicenter, retrospective case series. Issue 1 (14th October 2014) - Ravi, Sowmya; Spencer, Kristen; Ruisi, Mary; Ibrahim, Nageatte; Luke, Jason J; Thompson, John A; Shirai, Keisuke; Lawson, David; Bartell, Heddy; Kudchadkar, Ragini; Gunter, Ngoc Thi; Mehnert, Janice M; et al.
Abstract : Ipilimumab is a fully human, monoclonal antibody directed against Cytotoxic T Lymphocyte Antigen-4 (CTLA-4) that has demonstrated a survival benefit and durable disease control in patients with advanced melanoma. Ipilimumab is associated with potentially serious immune-related adverse events, including autoimmune hepatitis. Because clinical trials of ipilimumab excluded patients with pre-existing hepatitis B or C infection, there is a paucity of data on the safety of ipilimumab administration to that patient population. Here, we report the largest case series to date of patients with hepatitis B or C who received ipilimumab for advanced melanoma. Two of the nine patients described in this case series experienced fluctuations in their liver function tests (LFTs) and were subsequently treated with corticosteroids. Although this is a small series, the rate of hepatotoxicity appears similar to what has been seen in the general population treated with ipilimumab, and the ability to administer ipilimumab did not appear to be affected by concomitant hepatitis B or C infection. The use of ipilimumab in patients with metastatic melanoma who have pre-existing hepatitis can be considered among other therapeutic options.